2011
DOI: 10.1007/s00204-011-0714-1
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles induce apoptosis and G2/M arrest via PKCζ-dependent signaling in A549 lung cells

Abstract: The use of silver nanoparticles is one of the fastest growing product categories in the nanotechnology industry, with a focus on antimicrobial activity. However, thus far, toxicity data for silver nanoparticles are limited. In this study, we investigated the cytotoxic effects of silver nanoparticles (Ag NPs) and the pathway by which they affect A549 lung epithelial cells. The effects of Ag NPs on cell survival, cell cycle progression, and mRNA and protein alterations of selected cell cycle- and apoptosis-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 51 publications
3
58
2
5
Order By: Relevance
“…Exceptions were clusters 2 and 6, showing an upregulation of anti-apoptotic pathways for Caco-2 cells only. Apoptosis has often been reported to be induced by AgNPs through oxidative stress (Gopinath et al, 2010;Lee et al, 2011) and upregulation of anti-apoptotic pathways could be the result of an adaptation mechanism responding to stress, as previously reported in HepG2 cells exposed to AgNPs (Brzoska et al, 2015). As the Caco-2 cells in the present study appeared to have higher stress levels than the MCF-7 cells, possibly in these cells adaptation processes were activated.…”
Section: Mechanistic Responses In Caco-2 and Mcf-7 Cellssupporting
confidence: 82%
“…Exceptions were clusters 2 and 6, showing an upregulation of anti-apoptotic pathways for Caco-2 cells only. Apoptosis has often been reported to be induced by AgNPs through oxidative stress (Gopinath et al, 2010;Lee et al, 2011) and upregulation of anti-apoptotic pathways could be the result of an adaptation mechanism responding to stress, as previously reported in HepG2 cells exposed to AgNPs (Brzoska et al, 2015). As the Caco-2 cells in the present study appeared to have higher stress levels than the MCF-7 cells, possibly in these cells adaptation processes were activated.…”
Section: Mechanistic Responses In Caco-2 and Mcf-7 Cellssupporting
confidence: 82%
“…61 Lee et al 62 observed that the LDH level increased 210% when cells were cultivated for 48 hours in a culture medium containing AgNPs at 100 µg/mL, and found that AgNPs could induce the release of LDH in a concentrationand time-dependent manner, indicating that AgNPs reduced the membrane potential in A549 cells. We found that an IC 50 concentration of 6.0 µg/mL was significant to inhibit cell growth and sufficient to induce cell death.…”
mentioning
confidence: 99%
“…Such proposed mechanisms include complexing with thiol [1], sulfydryl, amino, or hydroxyl functional groups [13], competing with copper ions as a cofactor in transport or enzymatic reactions [13], general toxicity [13] [22], disruption of aliphatic carbon-hydrogen bonds by insertion of carbenes [23], DNA damage by arene-purine hydrophobic interactions [23], direct binding to DNA [1], increased permeability and disruption of cell membranes [1], and inhibition of respiratory [1] or signaling [21] enzymes.…”
Section: Introductionmentioning
confidence: 99%